Consumption of Sugar-Sweetened Beverages Is Related to Fasting Blood Glucose and the Nutritional Status among Young Adults in Indonesia - Syahranni, Dhanya; Kurniati, Ardesy Melizah; Liberty, Iche Andriyani; Husin, Syarif; Zulissetiana, Eka Febri (Faculty of Medicine Universitas Padjadjaran, 2025)
Background: Habitual consumption of sugar-sweetened beverages (SSBs) is linked to elevated blood glucose and increased body weight. Medical students often experience high stress, which may increase SSBs consumption. This study aimed to examine the associations between SSB consumption, fasting blood glucose, body mass index (BMI), and waist circumference among medical students.Methods: A cross-sectional study was conducted in October 2022 using a total sampling method involving 184 first-year students at the Faculty of Medicine Universitas Sriwijaya, Palembang, Indonesia. SSBs consumption was assessed using a semi-quantitative food frequency questionnaire (SQ-FFQ). Fasting blood glucose was measured by glucometer after an overnight fast. Body height, weight, and waist circumference were measured using a stadiometer, digital scale, and tape measure, respectively. Physical activity was assessed with the International Physical Activity Questionnaire–Short Form (IPAQ-SF). Associations were tested using Kruskall Wallis, independent t-test, and chi square as appropriate.Results: Most students consumed SSBs 3–4 times per week and in amount >495 mL. The volume of SSBs consumption was associated with BMI (p=0.02), fasting blood glucose (p<0.001), and waist circumference (p<0.01). Similarly, the frequency of SSBs consumption was associated with fasting blood glucose (p=0.04) and waist circumference (p<0.01), but not with BMI (p=0.16). Conclusion: Consumption of SSBs among students is high. Frequent and high-volume consumption of SSBs is associated with elevated fasting blood glucose levels and the nutritional status, whereas higher volume is associated with increased BMI. Reducing SSB intake and promoting healthier beverage choices may support a sustainable healthy lifestyle in young adults.